Transgressão e moralidade na formação de uma “matrona esclarecida”: contradições na filosofia de educação nisiana - Rosa, Graziela Rinaldi da (Universidade do Vale do Rio dos Sinos, 2012)
In this work we tried to reflect about the work of a 19th century Brazilian writer - Nizia Floresta. This is a qualitative research, nature of historiography and documentary base, that questions which education philosophy did Nizia Floresta defend in her work? We made research in paper of her time and in posthumous editions, theses, dissertations, articles and work of Nizia and about her. A search for documents at museums, churches, at Espaço Cultural Nizia Floresta, at schools, at public and historic archives and at The Institute of History (both in Rio Grande do Sul and Rio Grande do Norte) was made. This thesis presents the basic argument which Nizia Floresta, teacher and Brazilian 19th century writer, broke with, but, simultaneously, she kept some principles of the time, like, for example, the visibility of the feminine argument on the debate about the Brazilian education and, in particular, about women education. The rupture was the politicization of this reality and permanence was the maintenance of most of the content taught to women as well as the proposal for a moral education for girls. When making a rereading of texts and works of Nizia Floresta was made a survey of research on materials produced by Nizia and other traces that mark her beliefs around her education philosophy, including a theoretical dialogue with Latin American, particularly Marcela Lagarde y de Los Rios, Margarita Pisano and Heleieth Saffioti and Constância Duarte. When we contextualize Europe and Brazil that Nizia Floresta knew, and how were women life and their social role, we see how singular is the view of Nizia Floresta. Her education philosophy was analyzed from her works and educational institutions founded by her, as well as the girls habits at Colégio Augusto, the discipline, the punishments and studied contents. Were seen the virtues she taught to girls, and the relation between her thoughts and the thoughts of the Roman Catholic Church, Rousseau and Comte, with the ideals of social order, progress, abolitionism, moral education for girls, equity and gender relations between men and women. The thesis explains fundamental concepts in the Nizia Florestas education philosophy: educational reform, utilitarianism, family, moral education, social order, values and gender relations between men and women. We can see the relations of her work with Comte, the alliance that Floresta proposed between parents and other educational spaces, as well as her approximations with Rousseau and feminist theories. The relation with the abolitionism, the family model and the women role in the educational philosophy of Nizia are shown, as well as the contradictions found in her educational philosophy. We analyzed the dialogue between The Woman and the Priest, the importance of women, the lounges and andocentric logic that is present in the thoughts of both intellectuals. We compared utilitarian positivism and Florestas utilitarianism, Comtes scientism and Nizia?s educational philosophy, as well as the conception of education in the positive Republic and education proposed by Floresta. We investigated the conceptions of Revolution in Comte?s work and Floresta?s and the idea of progress in both works. We clarified how far positivism interfered in the Nizias education philosophy, as well as Comte?s view on women; the regular work and moral education vision; the understanding of metaphysics; the positive Republic, the point of order and altruism.
Keywords: Educação para meninas; Filosofia da educação; História da educação; Relações de gênero; Education for girls; Education philosophy; History of education; Gender relations; ACCNPQ::Ciências Humanas::Educação